Analysis of The Ability Student of SMA Al Islam Krian to Understanding Mathematical Concepts in Terms of Learning Styles - Berliana Putri Permatasari; Annisa Dwi Sulistyaningtyas (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
This research aims to analyze and describe the ability of students of SMA Al Islam Krian to Understanding Mathematical Concepts in Terms of Student Learning Styles for the 2022/2023academic year on the material of circle equations in terms of learning stylesusing include auditory, visual, and kinesthetic learning styles with a qualitative descriptive approach. The data collection techniques used were tests and interviews, with research instruments in the form of learning-style questionnaires, test questions, and interviews. The results of the study, it was found that from the visual learning style students with high abilities were able to understand mathematical concepts, whereas students with low abilities were not yet able to understand mathematical concepts. Meanwhile, from the auditory learning style, students with high and low abilities are less able to understand mathematical concepts. If from the kinesthetic learning style students with high abilities are less able to understand mathematical concepts, while students with low abilities are not yet able to understand mathematical concepts.